Spatial distribution patterns of metals in the bottom sediments of artificial reservoirs in south Sardinia, Italy (Journal of Nepal Geological Society, 2006)
The Flumendosa-Campidano system of artificial lakes is the major water resource for southern Sardinia, Italy. The main basins of this system are situated in ore-rich terrains which are responsible for the supply of different heavy metals in the bottom sediments forming in these lakes. The chemical and mineralogical composition of these materials reflects the lithology of the country rocks and is strongly influenced by the surrounding ore mineral occurrences. Because of the semiarid climate of this island, along with the uneven distributions of rains and increasing water demand, water levels in these lakes are prone to broad yearly variations and consequently their sediments are periodically prone to the action of the meteoric waters and of the atmosphere which causes oxidation and remobilisation of most metals. However the metal-rich sediments of the lakes appear at present sufficiently stable as elemental concentrations in the water reaching the treatment plants are normally below the permissible limits for drinking water. Metals re-precipitate in less soluble forms and accumulate in the deepest parts of the sedimentary piles which would act as a trap for the metals. Data on metal contents in the sediments are examined in view of deriving pollution risks. Distribution maps have been drawn for each element for assessing its dispersion and accumulation effects. The mapping together with statistical treatment of the results and comparison with previous data has shed light on the origin and distribution of the various pollutants.